The Compounds Activity of Black Potato (Plectranthus rotundifolius) as an Antioxidant Nutraceutical: - - Fitriyani; Natasya, Cindy; Safrina, Maureta E. R.; Ningrum, Salsabila E. S.; Zahra, Lisa A.; Ma’arif, Burhan (Pharmaceutical Journal of Indonesia, 2022)
Black potato (Plectranthus rotundifolius) is one of the horticultural plants that has potential as nutraceutical food and also contain bioactive compounds such as being rich in flavonoids, especially anthocyanins. The potential benefits of black potatoes are not widely known by public, so it is necessary to cultivate one of them by processing it into food such as instant porridge, which is then labeled as B-PORIS product. The reason for choosing instant porridge was because it is a practical food product. This research aimed to prove that instant porridge from black potato contains bioactive compounds flavonoids, especially anthocyanins. These instant porridges are made with the appropriate ratio in 3 formulations with different parameters of black potato flour concentration, formulation 1 10%, formulation 2 9%, and formulation 3 11%. This research was conducted with organoleptic tests, moisture content tests, flavonoids, anthocyanins, and hedonic tests. The results of the organoleptic test obtained soft texture, characteristic chocolate smell, brown color, and slightly sweet and sweeter taste. The results of moisture content test were qualified with water content of not more than 7%. The results of flavonoid and anthocyanin test obtained positive results in all of formulations. The hedonic test result 80-90% of panelists indicate choose an option like, and really like in questionnaires, results demonstrated that formulation 3 was most likely. So it can be concluded that black potato tubers has the potential to become a nutraceutical product as an instant porridge with antioxidant effect that received and liked by various groups of age.